Management of myelomeningocele in the Caribbean; A plastic surgery perspective - Miguel A. Johnson; Peyton Lawrence; Christian V. Eisenring; Preci Hamilton (Elsevier, 2020)
Meningomyelocele (MMC) has been a prevalent disease in the Caribbean due to insufficient primary prevention in the low socio-economic population.We present a female neonate with sacral MMC, macrocephaly and talipes equine vara.The MMC was surgically repaired within 24 hour with closure of the resultant defect using rotational advancement flaps and subsequent insertion of a low pressure ventriculoperitoneal shunt.MMC repair is performed only in very few centers within the Caribbean. The size of the MMC defects creates unique challenges for the reconstructive surgeon and several factors need to be considered in selecting the best method for closure. We present a case of a large defect and discuss our operative approach to achieve successful closure.